The Effect of Essential Oil Formula and Para Menthane Diol on Mortality and Oviposition Deterrent of Brown Planthopper - Tri Lestari Mardiningsih; NFN Rismayani; NFN Ma'mun (Pusat Penelitian dan Pengembangan Perkebunan, 2019)
Essential oils such as clove, lemongrass, and citronella are known as botanical insecticides. Mixed-essential oils and a single compound of the oil itself may increase its efficacy. The experiment aimed to examine the effect of the essential oil mixture and para-menthane-3,8-diol (PMD) formulas in inhibiting of the egg-laying and mortality of brown planthopper. The study conducted at the greenhouse of Indonesian Spices and Medicinal Crops Research Institute, Bogor. The formula tested were clove+citronella oils (1:1), clove+lemongrass oils (1:1), the single essential oil, solvent materials (a mixture of tween 80, Turpentine, and surfactant), PMD-solvent substances (emulsifier, alcohol 96%, and surfactant). A contact application was applied to the insect. Observation parameters were egg numbers laid and brown planthopper adult and nymph mortalities. The result of the insect contact application method showed that adult mortality was not significantly different compare with control and synthetic insecticide. Based on the plant residue test, nymph mortality due to clove oil + citronella oils were not significantly different from control and insecticide. Meanwhile, based on the insect and plant spray test, adult mortality on clove oil + citronella was not differently significant from the synthetic insecticide. However, the effectiveness of clove+lemongrass oils was slower. The efficacy of the oil formula to the egg laid was significantly different from the synthetic insecticide treatment, i.e., fewer eggs laid. PMD was less effective than the essential oil formula on the nymphs and adult mortalities of brown planthopper. Further field evaluations of the clove oil + citronella formulas are required.